Implementing Learner Training: A Case Study - Linda Bawcom (Networks: An Online Journal for Teacher Research, 2002)
In a learning environment where there are varying levels of proficiency, and knowing that I do not have enough class time to assist the very low level students as much as they need, I hope to present them with skills necessary to take responsibility for the management of their own learning (see Hill 1994; Oxford 1990; Clark 1987). I argue that the implementation of learner training, in addition to giving students choice, enables them to solve some of their own problems (see Allright 1990; Yalden 1987). Thus, along the lines suggested by Cohen and Manion (1985: 220-21) with regard to action research, this experiment begins with the identification of the problem to be solved and is followed by a review of literature on the subject. Once the material is created or adapted, the experiment is implemented, data is collected, and finally interpreted and evaluated.